Evaluation in environmental conservation: issues of adequacy and rigour. (11th December 2008) - Lowe, Arianne; Dovers, Stephen; Lindenmayer, David; Macdonald, Bennett
Significant effort and investment is committed to environmental conservation. How much conservation projects can achieve will be determined by the efficacy of this investment. Measuring project performance, establishing priorities and expenditure options requires examination of the relationship between goals, inputs and outcomes, based on clear evaluation methods. This paper reviews the recent status of project evaluation reported in the published, peer-reviewed environmental literature. The review: (1) estimates the frequency of published evaluations to be approximately 0.17% and, importantly (2) identifies the methodological foundations. This article finds that while there has been a recent increase in attention to evaluation in environmental conservation, there remains: (1) a paucity of peer-reviewed published evaluations (2) inadequate guidance on evaluation methods. Factors contributing to this situation are explored. This paper concludes that the methods and application of evaluation in environmental conservation – and thus the effectiveness of management – can be improved, and indicates how.